Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Multipel Representasi pada Materi Larutan Elektrolit dan Non Elektrolit - Indriani, Anggun Tyra; Yuniar, Yuniar; Pratiwi, Ravensky Yurianty (Orbital: Jurnal Pendidikan Kimia, 2023)
This research aims to produce valid student worksheets (LKPD) based on multiple representations on electrolyte and non-electrolyte solution material and to determine student responses to the LKPD that has been developed. This research is research and development. The research design uses the ADDIE model, but only up to the development stage. Data collection instruments used interview sheets, validation sheets and questionnaires. LKPD validation involves 3 validators, namely media, material and language experts. The subjects in this study involved 3 students for one-t-one trials and 12 students for small group trials. The research results showed that the LKPD developed was very valid with a percentage of 85,82%, of which 89,13% of the media expert validators were in the very valid category, 85,00% of the material expert validators were in the very valid category and 83,33% of the language validators were in the very valid category. Students' responses to LKPD based on multiple representations on electrolyte and non-electrolyte solution material were categorized as very good with a percentage of 91,83%, where one-to-one trials obtained a percentage of 90,27% with a very good and test category. Trying a small group (small group trial) obtained a percentage of 93,40% in the very good category.